Republic of Madagascar : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper on the Republic of Madagascar reports on the several key themes associated with longer-term development issues in Madagascar. As one of the poorest countries in sub-Saharan Africa, Madagascar suffers from low levels of social indicators across all fronts including education, health, water and sanitation, and infrastructure. To make progress toward the Millennium Development Goals, the country will need to scale up substantially both public and private investment while taking actions to increase absorptive and institutional capacity and implementing supportive policies in each of the priority sectors.